Selective Incivility as Modern Discrimination in Organizations - Cortina, Lilia M.; Kabat-Farr, Dana; Leskinen, Emily A.; Huerta, Marisela; Magley, Vicki J. (Journal of Management, 2013)
This collection of studies tested aspects of Cortina’s theory of selective incivility as a “modern” manifestation of sexism and racism in the workplace and also tested an extension of that theory to ageism. Survey data came from employees in three organizations: a city government (N = 369), a law enforcement agency (N = 653), and the U.S. military (N = 15,497). According to analyses of simple mediation, target gender and race (but not age) affected vulnerability to uncivil treatment on the job, which in turn predicted intent to leave that job. Evidence of moderated mediation also emerged, with target gender and race interacting to predict uncivil experiences, such that women of color reported the worst treatment. The article concludes with implications for interventions to promote civility and nondiscrimination in organizations.